2018
DOI: 10.22373/biotik.v5i2.3025
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Melalui Modul Berbasis Konstruktivisme Dalam Upaya Mengatasi Miskonsepsi Peserta Didik Pada Konsep Sel Di Sma Negeri 2 Sabang

Abstract: This study was designed to determine the effort of learning through constructivism-based module to overcome student’s misconceptions of Cell concept in SMAN 2 Sabang. The data collection was conducted in 2016, July to August. The method used in this research was quasi-experimental with one group pretest posttest design. The research was conducted in three classes, i.e. XI IA 1, 2 and 3 with 80 students in total. The instrument used was constructivism-based module and pretest-posttest diagnostic tests with CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
1
1
Order By: Relevance
“…The concepts of endocytosis and osmosis include submaterial membrane transport. In the research of Fitria et al (2017) reveald that students experienced a misconception of membrane trasnport submaterial by 17%, this result was lower than the findings in this research which showed that students experienced the highest misconception on endocytosis concept which is 63,33% and osmosis 51,67%.…”
Section: Figure 1 Conception Profile Diagram Of High School Students ...contrasting
confidence: 68%
See 1 more Smart Citation
“…The concepts of endocytosis and osmosis include submaterial membrane transport. In the research of Fitria et al (2017) reveald that students experienced a misconception of membrane trasnport submaterial by 17%, this result was lower than the findings in this research which showed that students experienced the highest misconception on endocytosis concept which is 63,33% and osmosis 51,67%.…”
Section: Figure 1 Conception Profile Diagram Of High School Students ...contrasting
confidence: 68%
“…In foregoing studies, it became apparent that students experienced misconceptions in cell material, essentially in Fitria et al (2017), Students at State High School 2 Sabang experienced misconceptions about the concept of cells, namely 13% of the cell chemical components submaterial, 24% of cell structure and function, organelle sub material of animal and plant cells were 17% and the transport mechanism through the membrane sub material was 12%. Meanwhile, research conducted by Rafika et al (2015) showed that there were misconceptions in the sub-material structure and function of cell organelles with an average percentage of misconceptions of 17.97%.…”
Section: Introductionmentioning
confidence: 99%
“…Perubahan kurikulum dari Kurikulum Tingkat Satuan Pendidikan (KTSP) menjadi Kurikulum 2013 (K13) berdampak besar bagi dunia pendidikan di Indonesia, terutama dalam kegiatan pembelajaran, seperti kesiapan dan kemampuan guru Biologi untuk mengajar, kesulitan yang terjadi dalam proses pembelajaran serta belum tersedianya buku teks. Salah satu dampak yang sangat berpengaruh dari perubahan kurikulum yaitu terjadi kesalahan dalam penafsiran dan proposisi konsep, sehingga terjadi kesalah pahaman pada konsep materi pembelajaran yang diterima oleh peserta didik (Fitria, 2017). Materi pembelajaran (instructional materials) merupakan bahan yang diperlukan untuk pembentukan pengetahuan, keterampilan, dan sikap yang harus dikuasai peserta didik dalam rangka memenuhi standar kompetensi yang ditetapkan.…”
Section: Pendahuluanunclassified